2021
DOI: 10.1007/s11606-020-06515-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Advancement in Academic Medicine: the Perception Gap Between Majority Men and Other Faculty

Abstract: BACKGROUND: According to the American Association of Medical Colleges, women comprise 26% of full professors and 19% of medical school department chairs. African American and Latino faculty comprise 4.6% of full professors and 6.9% of department chairs. OBJECTIVE: Because of the lack of representation of women and racial/ethnic minority faculty at the highest levels of academic medicine, this study examines the perceptions of barriers to advancement by men and women academic medical school faculty of differing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Effective interventions will require investment. Leadership—the majority of whom are not Black—must have an enriched understanding of the racist barriers to advancement in AM and work with intentionality to promote students, trainees, and faculty belonging to minoritized racial and ethnic groups …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective interventions will require investment. Leadership—the majority of whom are not Black—must have an enriched understanding of the racist barriers to advancement in AM and work with intentionality to promote students, trainees, and faculty belonging to minoritized racial and ethnic groups …”
Section: Discussionmentioning
confidence: 99%
“…17,50,51 Despite deeply rooted anti-Black racism permeating AM, participants were not aware of comprehensive interventions for faculty. Many AM centers offer implicit bias training; however, our study underscores that an effective antiracist intervention must be more comprehensive.…”
mentioning
confidence: 99%
“…Consistently, the limited literature that exists only captures Black women's experiences as aggregate with minoritized and underrepresented populations. Such literature may include several racial and ethnic groups or white women ( 23 , 24 ), or highlights the experiences of Black women as patients or physicians ( 25 27 ). While we may draw inferences about Black women medical students and residents from such research, we cannot fully understand how Black women conceptualize their medical school journey until we have research that allows them to directly speaks from their lens.…”
Section: Review Of Literaturementioning
confidence: 99%
“…7 In a study conducted among one universityÕs medical faculty, Bateman and colleagues found that implicit or unconscious biases about gender and race or ethnic-ity were barriers to career advancement for women and members of racial or ethnic minority groups. 16 In any health careÐrelated setting, when such malalignments and biases are the norm, discrimination and daily microaggressions occur and have adverse effects on workersÕ physical and mental health. 17 Muirhead and colleagues have reported that the lack of racial and ethnic diversity in nursing Òhas significant influence on educational experiences, workplace satisfaction, and career progressionÓ in all areas of nursing.…”
Section: Introductionmentioning
confidence: 99%